Lateral cephalometric diagnosis of asymmetry in Angle Class II subdivision compared to Class I and II - Meloti, Aparecida Fernanda [UNESP]; Gonçalves, Renata De Cássia [UNESP]; Silva, Ertty; Martins, Lídia Parsekian [UNESP]; Santos-pinto, Ary Dos [UNESP] (Dental Press International, 2014)
INTRODUCTION:Lateral cephalometric radiographs are traditionally required for orthodontic treatment, yet rarely used to assess asymmetries.OBJECTIVE: The objective of the present study was to use lateral cephalometric radiographs to identify existing skeletal and dentoalveolar morphological alterations in Class II subdivision and to compare them with the existing morphology in Class I and II relationship.MATERIAL AND METHODS:Ninety initial lateral cephalometric radiographs of male and female Brazilian children aged between 12 to 15 years old were randomly and proportionally divided into three groups: Group 1 (Class I), Group 2 (Class II) and Group 3 (Class II subdivision). Analysis of lateral cephalometric radiographs included angular measurements, horizontal linear measurements and two indexes of asymmetry that were prepared for this study.RESULTS:In accordance with an Index of Dental Asymmetry (IDA), greater mandibular dental asymmetry was identified in Group 3. An Index of Mandibular Asymmetry (IMA) revealed less skeletal and dental mandibular asymmetry in Group 2, greater skeletal mandibular asymmetry in Group 1, and greater mandibular dental asymmetry in Group 3.CONCLUSION:Both IDA and IMA revealed greater mandibular dental asymmetry for Group 3 in comparison to Groups 1 and 2. These results are in accordance with those found by other diagnostic methods, showing that lateral cephalometric radiography is an acceptable method to identify existing skeletal and dentoalveolar morphological alterations in malocclusions.

INTRODUÇÃO:as telerradiografias laterais são tradicionalmente solicitadas para planejamento ortodôntico, mas raramente utilizadas para avaliar assimetrias.OBJETIVO: o objetivo do presente estudo foi utilizar as telerradiografias laterais para identificar as alterações morfológicas esqueléticas e dentoalveolares existentes na má oclusão de Classe II subdivisão e compará-las com a morfologia existente nas más oclusões de Classe I e II.MÉTODOS:noventa telerradiografias laterais iniciais de adolescentes brasileiros de ambos os sexos, com idade cronológica entre 12 e 15 anos, foram divididas em três grupos randomizados e proporcionais: Grupo 1 (Classe I), Grupo 2 (Classe II) e Grupo 3 (Classe II subdivisão). A análise das telerradiografias laterais envolveu mensurações angulares, mensurações lineares horizontais e dois índices de assimetria, estipulados para o presente estudo.RESULTADOS:foi identificada, de acordo com o Índice de assimetria dentária (IAD), uma maior assimetria dentária inferior no Grupo 3. O Índice de assimetria mandibular (IAM) revelou menor assimetria esquelética e dentária no Grupo 2, maior assimetria esquelética no Grupo 1 e maior assimetria dentária inferior no Grupo 3.CONCLUSÃO:o IAD e o IAM mostraram maior assimetria dentária inferior no Grupo 3 do que nos Grupos 1 e 2. Esses resultados estão de acordo com os encontrados em outros métodos de diagnóstico, indicando que a telerradiografia lateral é um método aceitável para avaliar alterações morfológicas esqueléticas e dentoalveolares nas más oclusões.
Keywords: Facial asymmetry; Malocclusions; Radiography; Cephalometry; Assimetria facial; Má oclusão; Radiografia; Cefalometria